GAYA BAHASA METAFORA DALAM LIRIK LAGU, ‘’ BERTAUT’’ , KARYA NADIN AMIZAH - Maria Anggraini Devira Bria; Semuel H. Nitbani; Margareta P.E. Djokaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study focuses on the forms and significations of metaphors in the lyrics of the song "Bertaut" by Nadin Amizah. This study aims to discover the forms and meanings of metaphors in the lyrics of "Bertaut" by Nadin Amizah. This study employs Ulman's metaphor theory. This study employs a qualitative methodology using a descriptive technique. This research analyzes the metaphorical language styles in the lyrics of "Bertaut" by Nadin Amizah. This data comprises words, phrases, clauses, and sentences with metaphorical aspects, along with their interpretations in each lyric of the song "Bertaut" by Nadin Amizah. The study findings indicate that the metaphoric forms included in the lyrics of the song "Bertaut" encompass anthropomorphic metaphors, animal metaphors, and abstract-to-concrete metaphors. The metaphors in the lyrics of the song "Bertaut" illustrate the profound connection between a mother and child, portraying the mother as the ultimate sanctuary for expressing a range of emotions, from joy to sorrow, and as a refuge during tumultuous times.